Senescence of alveolar epithelial cells impacts initiation and chronic phases of murine fibrosing interstitial lung disease - Yamada, Zento; Nishio, Junko; Motomura, Kaori; Mizutani, Satoshi; Yamada, Soichi; Mikami, Tetuo; Nanki, Toshihiro (Frontiers in Immunology, 2022)
Fibrosing interstitial lung disease (ILD) is developed in the abnormal repair process of lung tissue damage. Cellular senescence has been reported to contribute to the progression of fibrosis. However, the mechanisms by which these senescent cells initiate and/or drive the progression of lung tissue fibrosis is not yet fully understood. We demonstrated that p21WAF1/CIP1- and p16INK4A-pathway-dependent senescence in type 2 alveolar epithelial cells (AEC2) were both involved in the initiation and progression of lung fibrosis in murine bleomycin (BLM)-induced ILD. p21WAF1/CIP1- senescent AEC2 emerged rapidly, as early as one day after the intratracheal instillation of BLM. Their number subsequently increased and persisted until the later fibrosis phase. Very few p16INK4A-senescent AEC2 emerged upon the instillation of BLM, and their increase was milder and slower than that of p21WAF1/CIP1+ AEC2. AEC2 enriched with senescent cells sorted from BLM-ILD lungs expressed senescence-associated secretory phenotype (SASP)-related genes, including Il6, Serpin1, Tnfa, Ccl2, Tgfb, and Pdgfa, at the initiation and chronic phases of fibrosis, exhibiting distinct expression patterns of magnitude that were dependent on the disease phase. Ly6C+ inflammatory monocytes increased in the lungs immediately after the instillation of BLM and interstitial macrophages increased from day 3. The expression of Acta2 and Col1a1 was up-regulated as early as day 1, indicating the activation of fibroblasts. We assumed that IL-6, plasminogen activator inhibitor-1 (PAI-1), and TGF- contributed to the accumulation of senescent cells along with the progression of fibrosis in autocrine and paracrine manners. We also considered CCL2, produced in large amounts by senescent AEC2, to have induced the infiltration of Ly6c+ inflammatory monocytes in the early phase and that TGF-b and PDGFa from senescent AEC2 contributed to the activation of fibroblasts in the very early phases. Our study indicated that senescent AEC2 play a role in the pathogenesis of fibrosing ILD throughout the course of the disease and provide insights into its pathogenesis that may lead to the development of new therapeutic methods targeting senescent cells or SASP molecules.